2004
DOI: 10.1001/jama.292.4.442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Computer-Based Decision Aid on Knowledge, Perceptions, and Intentions About Genetic Testing for Breast Cancer Susceptibility

Abstract: N RECENT YEARS, GENETIC TESTING for inherited cancer predisposition has become widely available. [1][2][3] Initially, the use of such testing was limited to those enrolled in research studies at specialized medical centers. However, developments in testing technology and widespread publicity in the news media have led to increased testing for conditions such as breast cancer susceptibility 4,5 in primary care [6][7][8] and other settings, raising questions about how to adequately inform patients about their pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
250
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 269 publications
(268 citation statements)
references
References 54 publications
14
250
4
Order By: Relevance
“…Several studies suggest using cancer genetic testing decision aids before testing to better inform patients about testing and to assure that they have more accurate risk perceptions. [115][116][117][118] An example of a decision aid used before cancer genetic testing is the computer program "Breast Cancer Risk and Genetic Testing," which is a CD-ROM-based program designed to educate women about breast cancer, heredity, and the benefits and limitations of genetic testing. Users reported that this program was easy to use and provided beneficial educational information before the genetic counseling session, thus allowing the genetic counselors to spend more time discussing specific individual risks and specific psychological concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies suggest using cancer genetic testing decision aids before testing to better inform patients about testing and to assure that they have more accurate risk perceptions. [115][116][117][118] An example of a decision aid used before cancer genetic testing is the computer program "Breast Cancer Risk and Genetic Testing," which is a CD-ROM-based program designed to educate women about breast cancer, heredity, and the benefits and limitations of genetic testing. Users reported that this program was easy to use and provided beneficial educational information before the genetic counseling session, thus allowing the genetic counselors to spend more time discussing specific individual risks and specific psychological concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Users reported that this program was easy to use and provided beneficial educational information before the genetic counseling session, thus allowing the genetic counselors to spend more time discussing specific individual risks and specific psychological concerns. 117,118 During the first genetic counseling session, a counselor must evaluate an individual's psychological and cognitive functioning and assess their capacity to provide informed consent for testing. Inability to process information secondary to active psychiatric or cognitive impairment could interfere with informed consent.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike population-based studies (see above), studies investigating genetic knowledge and attitudes in patients usually concentrate on specific disease-related issues [e.g., [15][16][17][18]. The present study aimed to investigate knowledge and attitudes related to genetics and genetic testing in general, among patients with chronic illnesses (e.g., diabetes, heart disease, musculoskeletal disease).…”
Section: Introductionmentioning
confidence: 99%
“…Though computer-based curricula aimed at educating patients have been shown to be effective at increasing knowledge about genetic testing for inherited breast cancer, 46,47 educating time-constrained physicians is challenging, and perhaps our goals should shift toward increasing availability of and referrals to genetic counselors.…”
Section: Discussionmentioning
confidence: 99%